Does the IAB employment sample reliably identify maternity leave taking? A data report - Uta Schönberg (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2009)
The data set that researchers have used most often to study career interruptions due to childbirth in the German context is the German Socio-Economic Panel (GSOEP). An alternative data source is the much larger IAB Employment Sample (IABS). Although this data set does not include direct information on childbirth, mothers on maternity leave can potentially be identified. There are, however, two problems. First, the leave variable in the IABS does not distinguish between maternity leave and other leave taking, such as sick leave. Second, the child's birth month has to be inferred from the month in which the mother goes on maternity leave, which is likely to lead to measurement error in the time that the mother spends at home after childbirth. This paper investigates both problems, using an extended version of the IABS that supplements the social security records with direct information on childbirth from the German Pension Register. I find that for Western West German citizens, at least 90% of leave spells are due to maternity leave. The child's birth month is correctly estimated for at least 70%, and over- or underestimated by one month for about 25% of mothers. I conclude that the most recent scientific use files of the IABS, the IABS 75-01 and IABS 75-04, provide a very valuable alternative data source to the GSOEP to study career interruptions due to childbirth, as long as the focus is on women who are attached to the labour market.
Keywords: 330; Erziehungsurlaub - Messung; IAB-Beschäftigtenstichprobe; Mütter; Erwerbsunterbrechung - Dauer; erwerbstätige Frauen; Elternzeit; Datenqualität